Borrower Related Factors Influencing Loan Repayment Performance in Omo Microfinance Institutions in Wolaita Sodo Town - Sintayehu Sibera Mehale (International Journal of Applied Sciences: Current and Future Research Trends, 2020)
The objective of this study was to analyze borrower related factors that influence loan repayment performance of microfinance institutions in Wolaita Sodo Town Southern Ethiopia. A total of 330 respondents, selected through systematic random sampling method were involved in this study. Primarily data were collected from respondents through structured questionnaire and secondary data were collected from records from microfinance institution. Descriptive statistics and Binary Logit model were employed to achieve the objectives. The results demonstrated that age, educational level, additional income from other activity and loan diversion were factors they showed significant association with loan repayment performance. Compared to male borrowers, females’ barrowers were found to be better in terms of loan repayment performance. However, number of dependents has no effect on loan repayment. Hence the institution is recommended to give attention for low educated borrowers and income of borrowers with great care and should take a corrective action accordingly.